Stratergi Pembelajaran Edutaiment Dalam Pembelajaran - Rizka Zulmi; Karlina Putri; Gusmaneli Gusmaneli (Politeknik Kampar, 2024)
The use of learning strategies that combine aspects of entertainment is known as